2008
DOI: 10.1002/app.28593
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of recycled polystyrene used for TV backset

Abstract: The recycled polystyrene (rPS) was toughened with ethylene-octylene copolymer thermoplastic elastomer (POE) and high-density polyethylene (HDPE) with various melt flow index (MFI), compatibilized by styrene-butadiene-styrene copolymer (SBS) to enhance the toughness of rPS for use as TV backset. The rPS/POE binary blends exhibited an increased impact strength with 5-10 wt % POE content followed by a decrease with the POE content up to 20 wt %, which could be due to poor compatibility between POE and rPS. For rP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The polymer applied for all tests was a general purpose polystyrene (GPPS) supplied by Tabriz petrochemical with density of 1.04 g/cm 3 , MFI of 11 g/10 min, break stress and strain of 45 MPa and 2%, respectively. SBS and EOC were applied as impact modifier for polystyrene matrix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polymer applied for all tests was a general purpose polystyrene (GPPS) supplied by Tabriz petrochemical with density of 1.04 g/cm 3 , MFI of 11 g/10 min, break stress and strain of 45 MPa and 2%, respectively. SBS and EOC were applied as impact modifier for polystyrene matrix.…”
Section: Methodsmentioning
confidence: 99%
“…SBS with trade name of styroflex 2G66 (65 w% of styrene) and MFI of 13 g/10min was prepared from BASF. This grade had density of 1 g/cm 3 , yield stress of 4 MPa, minimum break strain of 300%, and hardness of 84 Shore A. Ethylene octene plastomer (EOC), grade of Exact 0203 was obtained from ExxonMobil Co, USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, findings from other articles have shown that EPS tended to have poorer material properties than raw PS 26,27 ; this hampered the demand for the former material.…”
Section: Introductionmentioning
confidence: 98%
“…Compared with other methods, the solution evaporation method for WEPS reuse has the following advantages: requiring low temperature, no decrease in the molecular weight of PS and nearly no differences in comparison with those prepared by suspension polymerisation . However, PS has many limitations, such as brittleness, low impact strength and weak heat resistance, particularly low tensile strength . In overcoming these disadvantages, the focus is the process of modifying PS.…”
Section: Introductionmentioning
confidence: 99%